Reduced productivity after sickness absence due to musculoskeletal disorders and its relation to health outcomes - Lötters, Freek; Meerding, Willem-Jan; Burdorf, Alex (Scandinavian Journal of Work, Environment & Health, 2005)
' ' OBJECTIVES ': 'This prospective cohort study quantified the reduced productivity of workers on full duty after sickness absence from a musculoskeletal disorder and determined the effect of health parameters such as perceived pain, functional disability, and general health on reduced productivity. ' ' METHODS ': 'Workers were included who were returning to work from 2- to 6-week sickness absence due to a musculoskeletal disorder. Self-administered questionnaires at baseline, after return to work, and at a 12-month follow-up were used to collect information on productivity and health status. Logistic regression analyses evaluated the determinants of reduced productivity and determined the level of productivity loss shortly after return to work. ' ' RESULTS ': 'Reduced productivity was prevalent for 60% of the workers after they returned to work, and for 40% still at the 12-month follow-up. The initial musculoskeletal disorder caused 75% of the productivity loss shortly after return to work and 60% at the follow-up. Among those with productivity loss, the median loss for an 8-hour workday was 1.6 hours shortly after return to work and also at the follow-up. Worse physical health, more functional disability, and poorer relations with the supervisor were associated with productivity loss shortly after return to work, whereas recurrent sick leave was the greatest predictor of productivity loss at the follow-up. ' ' CONCLUSIONS ': 'Reduced productivity was common among workers returning to full duty after sickness absence due to a musculoskeletal disorder. Productivity loss illustrates the importance of the timing of return to work, especially among workers with residual functional disability after return to work. Moreover, the supervisor should be engaged early in the return-to-work process to guarantee an early, sustainable, and productive return to work for the employee.
Keywords: health outcome; MSD; musculoskeletal disorder; presenteeism; productivity; productivity costs; return to work; sickness absence